Changes of androgens levels in menopausal women - Brzozowska, Maria; Lewiński, Andrzej (Menopause Review/Przegląd Menopauzalny, 2020)
Androgens play an important role in women’s health. They are responsible for the sexual well-being and for maintaining proper structure and function of genitourinary woman’s tract. In menopausal period a relative increase in androgens level is observed as a result of dramatic demise of estrogens and increase of sex hormone-binding globulin (SHBG). However, the response of target tissue depends on its ability to control androgens availability. In menopausal women the symptoms of both hyperandrogenemia and of androgens deficiency may be observed. Hyperandrogenemia may result in discrete symptoms, such as slight terminal facial hair grow, or worsening of scalp hair loss. Those symptoms should not be belittled in any of the cases, especially when their severity increases one should seek possible causes of postmenopausal hyperandrogenemia. Ovarian and adrenal aging, leading to a progressive decline in androgen levels, may exert detrimental effects on the quality of life. During menopause, changes in activation of particular brain spheres are connected with low sex hormone concentration and correlate with loss of sexual arousability. Hypoactive sexual desire dysfunction (HSDD) may be the direct result of androgens deficiency in menopausal women. It is the only evidence-based indication for the use of testosterone in women. However, before treatment, other diseases must be excluded that might alternatively be the cause of HSDD.